Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.4751036
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle magnetization measurements by a high sensitive nano-superconducting quantum interference device

Abstract: A high sensitive nano superconducting quantum interference device (nanoSQUID) operating as a magnetic flux to critical current transducer with a suitable feedback circuit is employed to measure the magnetization of ferrimagnetic iron oxide nanoparticles. An improved SQUID responsivity has been obtained by using a loop inductance asymmetry. Iron oxide nanoparticles having a mean diameter of 8 nm have been excited by applying a polarizing field in the plane of the nanoSQUID loop. The field dependence of the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…A fundamentally new suggestion of this work, as compared to the previous ones, is the use of asymmetric link-up of current leads. Asymmetric connection to the interferometer with two Dayem bridges was implemented in recent work [7]. A new point as compared to [7] is the use of a sharp change in the average value of the critical current under a change in the quantum number near Φ = (n + 0.5)Φ 0 .…”
Section: Introductionmentioning
confidence: 99%
“…A fundamentally new suggestion of this work, as compared to the previous ones, is the use of asymmetric link-up of current leads. Asymmetric connection to the interferometer with two Dayem bridges was implemented in recent work [7]. A new point as compared to [7] is the use of a sharp change in the average value of the critical current under a change in the quantum number near Φ = (n + 0.5)Φ 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Limits of the model I have shown that using the model presented here, which does not take the Josephson effect in NB-electrode joints into account, I cs (Φ a ) of NBSs is derivable. The result is triangular-shaped I cs (Φ a ) with one to two branches, as has been observed in several experiments [15,20,21,[35][36][37][38][39][40][41][42][43][44][45]. Now, let me discuss the limits in which the model works.…”
Section: Calculating Modulation Depth and Transfer Functionmentioning
confidence: 56%
“…At this point the current is switched off, and I c is calculated from the duration of the ramp 38 . This technique can also be used with a FLL scheme [38][39][40] . Sensitivity is limited by the accuracy in determining I c , which is described by the escape of a particle from a potential minimum.…”
Section: Critical Current Readout and Threshold Detectionmentioning
confidence: 99%